ENT 530 Social Media Portfolio: Urcookues / Zhafarina Marwanta - Marwanta, Zhafarina
With the development of times and technology with the existence of freemarket activities, we are required to keep up with our abilities and skills so that we can take advantage of skilled and professional business opportunities. Indonesia itself is also experiencing progress that has penetrated in various fields, one of which is the advancement of information technology, which directly makes this business's promotion spread quickly. Especially for beginner business people, they must take full advantage of this technological sophistication to compete with other competitors. The culinary industry in Indonesia is a very strategic business sector for economic development in Indonesia. Culinary is no longer just a product that serves to fulfill biological needs. Still, now culinary has become a new lifestyle among people to show others what they eat on their social media. Seeing these conditions, it would be excellent if you run a culinary business that targets the market among young people. This is related to the desire of young people who want to get cheap snacks but still have a delicious and contemporary taste. The need for snacks is currently desirable and enjoyed. One such food is chewy soft cookies. This type of cookie is starting to trend among young people today because of its soft texture but still has a slightly wet texture from the chocolate. We even give cookies from Urcookues, an ingredient that has extraordinary properties, namely collagen. Collagen is now in the hype because of its properties that are so good for the body, especially the skin. This triggered me to make cookies containing collagen a product highlight for working on this portfolio. Apart from cookies, I think that another product is still related to this main product, namely milk. But I chose a healthier type of milk, namely almond milk. Urcookues also provides menus that can be useful for yourself or gifts that can be gifted to others. The difference from other cookie shops, Urcookues provides the cookie dough itself for sale. The goal is that customers can express their own cookies during a pandemic like this at home. I also had the idea for Urcookues with a package menu, where the package uses a 'besek,' which is a traditional Indonesian container. In terms of packaging and supporting tools, we also use materials that do not contain plastic. Plastic is currently very troublesome for the earth because it is difficult to decipher. So, we are also participating in using eco-friendly tools. In addition to an attractive and useful product, an advertisement is needed to run according to a plan that produces the maximum possible number of customers. In an advertisement, it also requires interesting words that can attract potential customers to buy our products, called copywriting. Using copywriting for an online business is like using a salesperson to attract potential customers to buy our products and services, only this salesman is writing. Copywriting is crucial in the online business world because it can invite potential customers to know and get to know the products or services that a business has. Prospective customers can also find out what and the advantages of the product they have. At first, the prospect will only read, but you will feel attracted to the product and try it from that reading. This copywriting can persuade potential customers but in a more subtle way. Prospective consumers will not feel forced and forced. So, copywriting can be one strategy and can prove quite effective in advertising. If a business can make copywriting that is memorable, unique, and interesting, it can make people feel curious about the products and services offered. So in an online business, expertise in making copywriting is essential, including this Urcookues online business.v TABLE O